Does the Genomic Landscape of Species Divergence in Phaseolus Beans Coerce Parallel Signatures of Adaptation and Domestication? - Cortés, Andrés J.; Skeen, Paola; Blair, Matthew W.; Chacón-Sánchez, María I. (Frontiers in Plant Science, 2018)
Exploring the genomic architecture of species and populations divergence aids understanding how lineages evolve and adapt, and ultimately can show the repeatability of evolutionary processes. Yet, the genomic signatures associated with divergence are still relatively unexplored, leading to a knowledge gap on whether species divergence ultimately differs in its genetic architecture from divergence at other spatial scales (i.e., populations, ecotypes). Our goal in this research was to determine whether genomic islands of speciation are more prone to harbor within-species differentiation due to genomic features, suppressed recombination, smaller effective population size or increased drift, across repeated hierarchically nested levels of divergence. We used two species of Phaseolus beans with strong genepool and population sub-structure produced by multiple independent domestications each especially in Andean and Mesoamerican / Middle American geographies. We genotyped 22,531 GBS-derived SNP markers in 209 individuals of wild and cultivated Phaseolus vulgaris and Phaseolus lunatus. We identified six regions for species-associated divergence. Out of these divergence peaks, 21% were recovered in the four within-species between-genepool comparisons and in the five within-genepool wild-cultivated comparisons (some of the latter did retrieve genuine signatures of the well described multiple domestication syndromes). However, genomic regions with overall high relative differentiation (measured by FST) coincided with regions of low SNP density and regions of elevated delta divergence between-genepools (ΔDiv), independent of the scale of divergence. The divergence in chromosome Pv10 further coincided with a between-species pericentric inversion. These convergences suggest that shared variants are being recurrently fixed at replicated regions of the genome, and in a similar manner across different hierarchically nested levels of divergence, likely as result of genomic features that make certain regions more prone to accumulate islands of speciation and within-species divergence. In summary, neighboring signatures of speciation, adaptation and domestication in Phaseolus beans are influenced by ubiquitous genomic constrains, which may continue to fortuitously shape genomic differentiation at various others scales of divergence.